Predicting local control of choroidal melanomas following 106Ru plaque brachytherapy. Issue 2 (1st October 2010) - Papageorgiou, K I; Cohen, V M L; Bunce, C; Kinsella, M; Hungerford, J L
Abstract : Background: We evaluated the control rate of choroidal melanomas treated with 106 Ru plaque brachytherapy to identify the risk factors associated with local recurrence and lack of response. Methods: A retrospective review of 106 Ru plaque brachytherapy for patients with choroidal melanoma treated at St Bartholomew's Hospital, London. Survival analysis was used to assess associations between evaluated age, sex, location, foveal proximity, tumour base and height, presence of lipofuscin and subretinal fluid, apex dose, radiation rate and type of plaque with time to local recurrence. Logistic regression analysis was used to assess to evaluate the association between the same set of variables and lack of tumour response. Results: From January 2002 to December 2006 189 patients were treated. The follow-up ranged from 12 to 78 (median 33) months. None of the patients received adjuvant diode laser thermotherapy. The control rate was 85.7% (14 recurred while 13 did not respond). Of the patients who had local recurrence, univariate survival analysis demonstrated an association with younger patients, foveal proximity, preoperative subfoveal fluid and tumour base >11 mm. Age and foveal proximity remained significant in a Cox multiple variable model (p=0.03). Of the patients who did not respond, logistic regression analysis showed that lack of response was associated with a tumour height >5 mm, confirmed through multiple variable analysis (p=0.027). Conclusions: Tumours that are close to the fovea in young patients appear more likely to show local recurrence. Tumour height >5 mm was the only prognostic factor that determined lack of response. These results may be used to select which tumours require adjuvant therapy.